Carbon-based negative electrode active material, preparation method, secondary battery and electric device

By preparing carbon-based negative electrode active material with a gram capacity of 345mAh/g~355mAh/g and a powder compaction density of 1.55g/cm3 to 1.65g/cm3, the shortcomings in the circulation performance and energy reserve performance of existing secondary batteries are solved, and higher structural stability and electrochemical performance are achieved.

CN119852399AActive Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311675585.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-07
Publication Date
2025-04-18
Estimated Expiration
2043-12-07

AI Technical Summary

Technical Problem

The circulation performance and energy reserve performance of existing secondary batteries are difficult to meet the market's demand for higher demands, especially in terms of powder compaction density and gram capacity under high pressure.

Method used

A carbon-based negative electrode active material is provided, with a gram capacity of 345mAh/g to 355mAh/g, and the powder compaction density under 20000N pressure is 1.55g/cm3 or more and less than 1.65g/cm3. By controlling parameters such as particle size and particle size distribution, graphitization degree and specific surface area, the structural stability and electrochemical properties of the material are improved.

Benefits of technology

The carbon-based negative electrode active material has higher structural stability and electrochemical properties during the circulation process, significantly improving the circulation performance and energy density of the secondary battery, and meeting higher market requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852399A_ABST
    Figure CN119852399A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-based negative electrode active material, a preparation method, a secondary battery and an electric device. The gram volume of the carbon-based negative electrode active material is 345mAh / g to 355mAh / g, and the powder compaction density under the pressure of 20000N is more than 1.55 g / cm < 3 > and less than 1.65 g / cm < 3 >. The secondary battery prepared from the carbon-based negative electrode active material has relatively high energy density on the premise of good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a carbon-based negative electrode active material, a preparation method, a secondary battery and an electrical device. Background Art

[0002] In recent years, secondary batteries have been increasingly used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace, etc. The market has also put forward higher requirements on the service life and energy storage performance of secondary batteries.

[0003] Negative electrode active material is one of the important raw materials of secondary batteries and has a great influence on the electrical properties of secondary batteries. In order to meet the increasing market requirements, it is necessary to provide a negative electrode active material to improve the cycle performance of secondary batteries. Summary of the invention

[0004] The present application provides a carbon-based negative electrode active material, wherein the gram capacity of the carbon-based negative electrode active material is 345 mAh / g to 355 mAh / g, and the powder compaction density under a pressure of 20000 N is 1.55 g / cm 3 Above and less than 1.65g / cm 3 The secondary battery prepared by the carbon-based negative electrode active material has a high energy density while having good cycle performance.

[0005] In any embodiment, the powder compaction density of the carbon-based negative electrode active material under a pressure of 20000N is 1.57g / cm 3 ~1.62g / cm 3 .

[0006] In any embodiment, the powder compaction density of the carbon-based negative electrode active material under a pressure of 49000N is 1.73g / cm 3 Above and less than 1.84g / cm 3 The carbon-based negative electrode active material within the above range is beneficial to better improve the cycle performance of the secondary battery.

[0007] In any embodiment, the gram capacity of the carbon-based negative electrode active material is 346 mAh / g to 353 mAh / g. The gram capacity of the carbon-based negative electrode active material within the above range helps to improve the stability of the negative electrode active material during the cycle process, thereby improving the cycle performance of the secondary battery.

[0008] In any embodiment, the carbon-based negative electrode active material includes primary particles and secondary particles. Optionally, the number of primary particles in the carbon-based negative electrode active material is greater than or equal to the number of secondary particles in the carbon-based negative electrode active material, which helps to reduce the structural fragmentation of the active material due to expansion and contraction of the carbon-based negative electrode active material during the cycle, improve the structural stability of the carbon-based negative electrode active material, and thus improve the cycle performance of the secondary battery.

[0009] In any embodiment, the carbon-based negative electrode active material satisfies at least one of the following conditions:

[0010] a) Particle size distribution K is 1.0-1.6, and can be selected as 1.1-1.50, K = (Dv90-Dv10) / Dv50;

[0011] b) Volume distribution particle size Dv50 is 8 μm to 13 μm, and can be 9 μm to 12 μm;

[0012] c) The degree of graphitization is 88% to 95%, and can be optionally 90% to 95%.

[0013] Controlling the particle size and particle size distribution to meet the above range helps to reduce the side reactions of the carbon-based negative electrode active material and the irreversible consumption of active ions (such as lithium ions) during the cycle, thereby improving the cycle performance of the secondary battery. The graphitization degree of the carbon-based negative electrode active material within the above range helps to increase the energy density of the negative electrode active material and improve the cycle performance of the secondary battery.

[0014] In any embodiment, the specific surface area of ​​the carbon-based negative electrode active material is 1.25 m 2 / g~1.95m 2 / g, optional 1.25m 2 / g~1.85m 2 / g; tap density is 1.07g / cm 3 ~1.27g / cm 3 The specific surface area and / or tap density of the carbon-based negative electrode active material meeting the above range is helpful to reduce the side reactions of the negative electrode active material during the cycle process and improve the cycle performance of the secondary battery.

[0015] In any embodiment, the carbon-based negative electrode active material is artificial graphite. The negative electrode active material is widely available and has low cost, which helps to control the production cost of secondary batteries.

[0016] The second aspect of the present application provides a method for preparing a carbon-based negative electrode active material, comprising the following steps:

[0017] Provide raw materials;

[0018] Processing the raw materials to obtain intermediates;

[0019] Performing graphitization on the intermediate to obtain a graphitized product;

[0020] Screening the graphitized product to obtain a carbon-based negative electrode active material;

[0021] The gram capacity of the carbon-based negative electrode active material is 345 mAh / g to 355 mAh / g, and the powder compaction density under a pressure of 20000 N is 1.55 g / cm 3 Above and less than 1.65g / cm 3 .

[0022] The carbon-based negative electrode active material prepared by the method has suitable energy density and good cycle stability, and the secondary battery prepared by using the material has good cycle performance.

[0023] In any embodiment, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0024] In any embodiment, the temperature of the graphitization treatment is 2600°C to 3000°C.

[0025] In any embodiment, the graphitization treatment time is 10 hours to 50 hours.

[0026] In any embodiment, the raw material includes one or more of petroleum coke, needle coke, and asphalt coke, and needle coke can be selected.

[0027] In any embodiment, based on the total volume of the raw material, the volume proportion of the fiber-type structure in the raw material is greater than or equal to 55%, and can be optionally 58%-70%.

[0028] Raw materials with more fiber-type structures are conducive to improving the compaction density and gram capacity of graphite negative electrode active materials, so that the graphite negative electrode active materials retain a high degree of integrity during the compaction process, and the battery has a high cycle life and good energy density; but too high a proportion of fiber-type structures will increase the cost and expansion rate of graphite negative electrode active materials and deteriorate kinetic performance. Raw materials with a volume proportion of fiber-type structures within the above range have both low costs and good gram capacity of graphite, and the battery cell has a full life cycle kinetic window, thereby comprehensively improving the long-term cycle life and electrochemical performance of the battery.

[0029] In any embodiment, the processing of raw materials specifically includes the following steps: crushing, shaping and grading the raw materials to obtain a first precursor; granulating the first precursor to obtain a second precursor; and low-temperature carbonizing the first precursor and the second precursor to obtain the intermediate product.

[0030] In any embodiment, the first precursor satisfies at least one of the following conditions:

[0031] (1) The Dv50 particle size of the first precursor is 6.5 μm to 10.5 μm;

[0032] (2) the particle size distribution of the first precursor (Dv90-Dv10) / Dv50 is 1.05 to 1.75;

[0033] (3) The tap density of the first precursor is 0.55 g / cm 3 ~0.75g / cm 3 .

[0034] In any embodiment, the volume distribution particle size Dv50 of the second precursor is 11 μm to 15 μm.

[0035] By controlling the particle size and particle size distribution of the raw materials or intermediate materials of the negative electrode active material, a negative electrode active material with good specific surface area and particle size distribution can be obtained, which is helpful to obtain a negative electrode active material with a suitable powder compaction density, and can improve the wettability of the negative electrode active material and improve the cycle performance of secondary batteries prepared with carbon-based negative electrode active materials.

[0036] In any embodiment, the graphitized product of the first precursor and the second precursor are mixed in a mass ratio of (1:1) to (6:4), which can improve the structural stability of the negative electrode active material during the cycle process and help improve the cycle performance of the secondary battery.

[0037] The third aspect of the present application provides a secondary battery including a negative electrode plate, wherein the negative electrode plate includes a negative electrode collector and a negative electrode film layer arranged on at least one surface of the negative electrode collector, and the negative electrode film layer includes the carbon-based negative electrode active material described in the first aspect of the present application or the carbon-based negative electrode active material prepared by the method described in the second aspect of the present application.

[0038] In any embodiment, the negative electrode plate satisfies at least one of the following conditions:

[0039] (1) The compaction density of the negative electrode film layer is 1.5 g / cm 3 ~1.65g / cm 3 , optional 1.55g / cm 3 ~1.65g / cm 3 ;

[0040] (2) The specific surface area of ​​the negative electrode film layer is 0.7 m 2 / g~2m 2 / g, optional 1.0m 2 / g~1.6m2 / g;

[0041] (3) The porosity of the negative electrode film layer is 0.22 to 0.42, and can be optionally 0.27 to 0.37.

[0042] The negative electrode sheet meeting the above conditions helps the secondary battery to obtain a good energy density, reduce the side reactions of the negative electrode active material during the cycle, and / or the migration resistance of active ions (such as lithium ions), thereby improving the cycle performance of the secondary battery.

[0043] A fourth aspect of the present application provides an electrical device, comprising the secondary battery described in the third aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0045] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0046] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0047] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0048] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0049] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0050] Description of reference numerals:

[0051] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0052] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0053] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0054] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0055] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0056] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0057] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0058] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0059] Carbon-based negative electrode active materials are one of the important raw materials for secondary batteries and have a great influence on the electrical properties of secondary batteries. During the cycle of secondary batteries, active ions (such as lithium ions and sodium ions) are inserted and deinserted in carbon-based negative electrode active materials, causing carbon-based negative electrode active materials to expand and shrink continuously. After the graphitization treatment of the negative electrode active material, the orderliness of the material crystal structure is improved, which helps to improve the energy density of the negative electrode active material. However, after the graphitization degree of the negative electrode active material is increased, the interlayer spacing of the material crystal structure becomes narrower. During the cycle of the secondary battery, the interlayer spacing of the negative electrode active material is enlarged, which reduces the stability of the crystal structure of the negative electrode active material, resulting in cracking and breaking of the negative electrode active material, thereby reducing the cycle performance of the secondary battery. In addition, as the interlayer spacing of the crystal structure of the negative electrode active material becomes narrower, the powder compaction density of the negative electrode active material also increases. The increased powder compaction density can improve the energy density of the negative electrode active material, but it can reduce the wettability of the negative electrode active material or the negative electrode sheet with the electrolyte, increase the electron migration resistance and polarization loss, and affect the cycle performance of the secondary battery.

[0060] Based on this, the present application provides a carbon-based negative electrode active material that can improve the cycle performance of secondary batteries.

[0061] [Negative electrode active material]

[0062] The present application provides a carbon-based negative electrode active material, wherein the gram capacity of the carbon-based negative electrode active material is 345 mAh / g to 355 mAh / g, and the powder compaction density under a pressure of 20000 N is 1.55 g / cm 3 Above and less than 1.65g / cm 3 .

[0063] Herein, the term "gram capacity" refers to the ratio of the capacity that can be released by the carbon-based negative electrode active material to the mass of the carbon material. Generally speaking, the higher the gram capacity, the more conducive it is to improving the energy density of the secondary battery.

[0064] The gram capacity of the carbon-based negative electrode active material is in the range of 345mAh / g to 355mAh / g, the lattice expansion during the material cycle is relatively small, the crystal structure stability is good, and the irreversible consumption of active ions is reduced; at the same time, the carbon-based negative electrode active material has excellent capacitance, which can increase the energy density of the secondary battery, thereby improving the cycle performance of the secondary battery.

[0065] In some embodiments, the gram capacity of the carbon-based negative electrode active material is 346 mAh / g to 353 mAh / g. In some embodiments, the gram capacity of the carbon-based negative electrode active material is 347 mAh / g to 353 mAh / g. In some embodiments, the gram capacity of the carbon-based negative electrode active material is 345 mAh / g, 346 mAh / g, 347 mAh / g, 348 mAh / g, 349 mAh / g, 350 mAh / g, 351 mAh / g, 352 mAh / g, 353 mAh / g, 354 mAh / g or 355 mAh / g, or a range between any two of the above values.

[0066] When the gram capacity is within the range, the carbon-based negative electrode active material has excellent crystal structure stability and electric capacity, and significantly improves the cycle performance of the secondary battery.

[0067] The gram capacity can be measured by any known method in the art. For example, the negative electrode active material sample can be fully stirred and mixed with the conductive agent carbon black and polyvinylidene fluoride (PVDF) in a proper amount of solvent NMP according to a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet is used as the counter electrode, the polypropylene (PP) film is used as the isolation membrane, and the electrolyte is injected, wherein the electrolyte formula used is as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed according to a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. CR2430 button cells are assembled in an argon-protected glove box. At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the button cell was recorded. The ratio of the charging capacity of the button cell to the mass of the negative electrode active material sample is the gram capacity of the negative electrode active material.

[0068] In this article, the "compacted density" of the powder refers to the density of the powder to be tested under a preset pressure. The greater the compacted density of the powder, the higher the mass of the powder material per unit volume. For negative electrode active materials, the higher the compacted density of the powder, the higher the capacitance of the negative electrode active material, which is more conducive to increasing the energy density of the secondary battery. When the compacted density of the powder increases, the crystal interlayer spacing of the negative electrode active material will also decrease, and the lattice expansion change will increase, which is not conducive to the structural stability of the negative electrode active material.

[0069] In addition, after the compaction density of the negative electrode active material powder is increased, the porosity of the negative electrode active material is correspondingly reduced, and the wettability of the negative electrode active material in the battery electrode with the secondary battery electrolyte is affected, which is not conducive to the insertion and deinsertion of active ions in the negative electrode active material and the free migration of electrons, and affects the cycle performance of the secondary battery.

[0070] The method for measuring the compacted density of the powder can be any method known in the art. For example, referring to GB / T24533-2009, 1g of negative electrode active material powder is weighed and added to a bottom area of ​​1.327cm 2 The mold is pressurized to a specific pressure, such as 20000N or 49000N, and the pressure is maintained for 30s, then the pressure is released and maintained for 10s. The powder compaction density of the negative electrode active material under the selected pressure is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).

[0071] In the prior art, when the gram capacity of the negative electrode active material is in the range of 345 mAh / g to 355 mAh / g, it has a viscosity of not less than 1.65 g / cm2 under a pressure of 20,000 N. 3 The compaction density of the carbon-based negative electrode active material provided in the present application has a reduced powder compaction density within the gram capacity range, which not only makes the carbon-based negative electrode active material have an ideal energy density, but also makes the negative electrode active material have a lower volume expansion rate during the cycle, thereby improving the structural stability of the negative electrode active material and improving the cycle life of the secondary battery.

[0072] In some embodiments, the powder compaction density of the carbon-based negative electrode active material under a pressure of 20000N is 1.55 g / cm 3 , 1.56g / cm 3 , 1.57g / cm 3 , 1.58g / cm 3 , 1.59g / cm 3 , 1.60g / cm 3 , 1.61g / cm 3 、1.62g / cm 3 、1.63g / cm 3 , 1.64g / cm 3 , 1.65g / cm 3 Or the range between any two of the above values. In some embodiments, the powder compaction density of the carbon-based negative electrode active material under a pressure of 20000N is 1.57g / cm 3 ~1.62g / cm 3 , which can further improve the capacity and structural stability of the negative electrode active material and improve the cycle performance of the secondary battery.

[0073] In some embodiments, the powder compaction density of the carbon-based negative electrode active material under a pressure of 49000N is 1.73g / cm 3 Above and less than or equal to 1.84g / cm 3 .

[0074] In some embodiments, the powder compaction density of the carbon-based negative electrode active material under a pressure of 49000N is 1.75g / cm 3 , 1.76g / cm 3 , 1.77g / cm 3 , 1.78g / cm 3 , 1.79g / cm 3 , 1.80g / cm 3 、1.81g / cm 3 , 1.82g / cm 3 , 1.83g / cm 3 , 1.84g / cm 3 Or the range between any two of the above values ​​is helpful to better improve the capacity and structural stability of the negative electrode active material and improve the cycle performance of the secondary battery.

[0075] In some embodiments, the carbon-based negative electrode active material includes primary particles and secondary particles. Optionally, the number ratio of the primary particles in the carbon-based negative electrode active material is greater than or equal to the number ratio of the secondary particles in the carbon-based negative electrode active material, which helps to reduce the breakage of the negative electrode active material particles caused by expansion and contraction of the carbon-based negative electrode active material during the cycle, improve the chemical and mechanical stability of the carbon-based negative electrode active material, reduce the irreversible consumption of active ions, and achieve improved cycle performance of secondary batteries.

[0076] Herein, primary particles and secondary particles are both well-known in the art. Herein, "primary particles" refer to non-agglomerated particles. Herein, "secondary particles" refer to agglomerated particles formed by the aggregation of two or more primary particles.

[0077] Primary particles and secondary particles can be distinguished by observing the particle cross-section of the graphite negative electrode active material using a scanning electron microscope (SEM). In the present application, the proportion of the number of secondary particles in the graphite negative electrode active material can be tested by methods known in the art. As an example, a cross-section polisher (e.g., IB-09010CP argon ion cross-section polisher of JEOL, Japan) can be used to prepare the cross-section of the negative electrode sheet; then, referring to JY / T010-1996, a scanning electron microscope (e.g., Sigma 300 scanning electron microscope of ZEISS, Germany) is used to scan the cross-section of the negative electrode sheet, and multiple test areas are randomly selected in the test sample, and images of multiple test areas are obtained using a scanning electron microscope, and the number of graphite negative electrode active materials with secondary particle morphology in each image is counted. The ratio of the total number of graphite negative electrode active material particles, the average value of multiple statistical results is the number of secondary particles in the graphite negative electrode active material.

[0078] In some embodiments, based on the total number of primary particles and secondary particles in the graphite negative electrode active material, the number of primary particles may be 50%, 52%, 54%, 56%, 58%, 60% or any range therebetween.

[0079] During the cycle, the negative electrode active material undergoes repeated expansion and contraction deformation processes, resulting in the breakage of the negative electrode active material particles, which seriously reduces the mechanical integrity of the primary and secondary particles; at the same time, the broken particles increase the electrolyte penetration and side reaction degree, and increase the irreversible consumption of active ions. Graphite negative electrode active materials with a low proportion of secondary particles are conducive to maintaining the particle integrity of graphite negative electrode active materials during battery preparation, reducing the generation of new interfaces, reducing the consumption of active lithium during the cycle, and further improving the cycle stability of secondary batteries. At the same time, a certain number of secondary particles can reduce the expansion of the negative electrode sheet while taking into account the kinetic performance of the secondary battery, so that the battery cell has a kinetic window for the entire life cycle, and will not cause the battery capacity to decay sharply and the battery life to deteriorate sharply due to uneven current distribution, thereby comprehensively improving the cycle stability of the battery.

[0080] In some embodiments, the particle size distribution K of the carbon-based negative electrode active material is 1.0 to 1.6, K = (Dv90-Dv10) / Dv50, which can be optionally 1.1 to 1.5. In some embodiments, the particle size distribution K of the carbon-based negative electrode active material is 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.6 or a range between any two of the above values, which helps to improve the concentration of the particle size of the negative electrode active material, reduce the uneven distribution of active ions in the negative electrode active material due to the large difference in particle size, reduce the side reaction of the negative electrode active material with a smaller particle size and the electrolyte, and improve the cycle performance of the secondary battery.

[0081] In some embodiments, the volume distribution particle size Dv50 of the carbon-based negative electrode active material is 8 μm to 13 μm, and can be optionally 9 to 12 μm. In some embodiments, the volume distribution particle size Dv50 of the carbon-based negative electrode active material is 8.0 μm, 8.5 μm, 9.0 μm, 9.5 μm, 10.0 μm, 10.5 μm, 11.0 μm, 11.5 μm, 12.0 μm, 12.5 μm, 13.0 μm, or a range between any two of the above values, thereby shortening the path for active ion embedding and extraction, which is beneficial to improving the transport performance of active ions and electrons, and is also beneficial to forming a reasonable pore structure between the particles of the negative electrode film layer, thereby further improving the cycle performance and / or rate performance of the secondary battery.

[0082] In this application, the volume distribution particle size Dv50 of the carbon-based negative electrode material has a well-known meaning in the art, which respectively represents the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T 19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.

[0083] In some embodiments, the graphitization degree of the carbon-based negative electrode active material is 88% to 95%. In some embodiments, the graphitization degree of the carbon-based negative electrode active material is 90.4%, 91.1%, 92.3%, 93.5%, 94.1%, 94.7% or a range between any two of the above values, which is conducive to the negative electrode active material having excellent gram capacity and good active ion transport performance, thereby facilitating the secondary battery to have both high energy density and good kinetic performance.

[0084] In the present application, the graphitization degree of the carbon-based negative electrode active material has a well-known meaning in the art and can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JISK 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d002 of the C(002) crystal plane in the material crystal structure, and then the graphitization degree is calculated according to the formula g=(0.344-d002) / (0.344-0.3354)×100%. In the above formula, d002 is the average interlayer spacing of the C(002) crystal plane in the material crystal structure expressed in nanometers (nm).

[0085] The degree of graphitization reflects the completeness of the graphite crystal structure in the material, that is, the regularity of the arrangement of carbon atoms in the graphite structure in the material. A material with a high degree of graphitization indicates that the distance between graphite layers is small, the smaller the lattice rotation, the less scattered stacking of the layers, the more orderly the arrangement, and the higher the specific capacity of the material. A material with a low degree of graphitization indicates that the distance between graphite layers is large, which is conducive to the rapid deintercalation of active ions and the improvement of the battery's rate performance. The large distance between graphite layers means that the material expands less when lithium is inserted, which has the effect of shallow charge and shallow discharge. At the same time, the material has a low degree of graphitization, and the SP in the graphite material is low. 3 There are more bonds, which makes the layers of graphite material restrain each other, making the structure of graphite material more stable. The graphite material has excellent stability during the cycle and is conducive to long-term circulation.

[0086] In some embodiments, the specific surface area of ​​the carbon-based negative electrode active material is 1.25 m 2 / g~1.95m 2 / g, optional 1.25m 2 / g~1.85m 2 In some embodiments, the specific surface area of ​​the carbon-based negative electrode active material is 1.3 m 2 / g, 1.35m 2 / g, 1.45m 2 / g, 1.5m 2 / g, 1.55m 2 / g, 1.6m 2 / g, 1.65m 2 / g, 1.7m 2 / g, 1.75m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 1.95m 2 / g or a range between any two of the above values, which helps to reduce the side reactions between the negative electrode active material and the electrolyte, reduce the irreversible active consumption of metal ions, and improve the cycle performance of the secondary battery.

[0087] In some embodiments, the tap density of the carbon-based negative electrode active material is 1.07 g / cm 3 ~1.27g / cm 3 In some embodiments, the tap density of the carbon-based negative electrode active material is 1.1 g / cm 3 , 1.15g / cm 3 , 1.18g / cm 3 , 1.2g / cm 3 , 1.23g / cm 3 Or the range between any two of the above values ​​is helpful to improve the transmission performance of active ions and electrons and improve the kinetic performance of the secondary battery.

[0088] In some embodiments, the carbon-based negative electrode active material is artificial graphite.

[0089] [Method for preparing negative electrode active material]

[0090] The present application also provides a method for preparing a carbon-based negative electrode active material, the preparation method comprising the following steps: providing a raw material; processing the raw material to obtain an intermediate product; graphitizing the intermediate product to obtain a carbon-based negative electrode active material; the carbon-based negative electrode active material has a gram capacity of 345 mAh / g to 355 mAh / g, and a powder compaction density of 1.55 g / cm under a pressure of 20000 N. 3 Above and less than 1.65g / cm 3 The secondary battery prepared by the carbon-based negative electrode active material has a high energy density while having good cycle performance.

[0091] Herein, the term "graphitization treatment" refers to the high temperature heat treatment process of carbon materials, which is the process in which the carbon materials transform from a two-dimensional carbon network structure to a three-dimensional ordered structure through "microcrystal" growth under high temperature.

[0092] In some embodiments, the maximum power of the graphitization process is 70%-90% of the rated power of the graphitization process equipment.

[0093] In some embodiments, the power of the graphitization process may be selected to be 70%, 75%, 80%, 85%, 90% of the rated power of the equipment, or any range of values ​​therebetween.

[0094] It can be understood that graphitization equipment refers to any device capable of graphitization, including but not limited to Acheson furnace, box furnace, inner series furnace, continuous graphitization, electric calcining furnace, medium frequency furnace, tubular furnace, etc. The rated power of graphitization equipment produced by different manufacturers may be different, and you can choose according to the actual situation.

[0095] The graphitization treatment power used in this application needs to be lower than the rated power of the graphitization treatment equipment to achieve uniformity of the temperature field during the graphitization treatment process, ensure the consistency of the material's gram capacity, and help improve the cycle life of the battery.

[0096] In some embodiments, the graphitization treatment equipment is an inner series furnace, and the rated power of the inner series furnace is 25000W-32000W.

[0097] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the rated power of the Acheson furnace is 28000W-30000W.

[0098] In some embodiments, the temperature of the graphitization treatment is 2600°C to 3000°C.

[0099] In some embodiments, the temperature of the graphitization treatment is 2600° C., 2700° C., 2800° C., 2900° C., 3000° C., or any range therebetween.

[0100] In some embodiments, the graphitization treatment time is 10 hours to 50 hours.

[0101] In some embodiments, the graphitization treatment time is 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h, 50 h, or any range therebetween.

[0102] In some embodiments, the graphitization treatment equipment is an internal series furnace, and the graphitization treatment time at maximum power is 10h-30h.

[0103] In some embodiments, the graphitization treatment equipment is an Acheson furnace, and the graphitization treatment is performed at maximum power for 30 hours to 50 hours.

[0104] In some embodiments, the raw material includes at least one of petroleum coke, needle coke, and asphalt coke, and needle coke may be selected.

[0105] As used herein, the term "petroleum coke" refers to coke formed by high-temperature carbonization of petroleum residue or petroleum asphalt.

[0106] In this article, the term "needle coke" refers to coal tar pitch or petroleum pitch, which can generate coke with a needle-like texture after being carbonized in the liquid phase to generate an anisotropic intermediate phase and then subjected to processes such as high-temperature carbonization.

[0107] As used herein, the term "pitch coke" refers to a solid material produced by carbonizing coal tar pitch at high temperatures.

[0108] In some embodiments, the volume proportion of the fibrous structure in the raw material is greater than or equal to 55%, and can be optionally 58%-70%.

[0109] Among them, needle coke has a series of advantages such as low thermal expansion coefficient, low porosity, low sulfur, low ash, low metal content, high conductivity and easy graphitization, etc. The graphite material after graphitization can reach a high ultimate compaction density and has a low cyclic expansion rate.

[0110] Coke raw materials usually include at least one of mosaic, regional and fibrous structures. Usually, based on the morphological characteristics and isochromatic zone size of coke raw materials under a polarizing microscope, isochromatic zone microstructures with a size less than 30 μm are judged as mosaic, isochromatic zone microstructures with a size greater than 30 μm are judged as regional, and anisotropic strip-shaped isochromatic zones are judged as fibrous structures.

[0111] In this article, "fibrous structure" is also called streamlined structure, which refers to the structure of the raw material with obvious fibrous texture observed under a microscope.

[0112] In this application, the volume proportion of the fiber-type structure in the raw material can be tested by methods known in the art. As an example, take the raw material according to GB 1997-89, mix the raw material crushed to 1mm, shrink it to 40g~50g, use a square hole sieve to take 0.07mm~1.0mm grade sample 4g~5g for film making; prepare powder coke and block coke light film according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with clay, flatten it, and place it on the stage to align the focus, calibrate the microscope, and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) to make the field of view present the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the fiber-type structure optical organization by the total number of statistical testing points as the volume proportion of the fiber-type structure in the raw material.

[0113] In some embodiments, based on the total volume of the raw material structure, the proportion of the fiber-type structure in the coke raw material can be selected as 55%, 58%, 60%, 63%, 65%, 68%, 70% or any range of values ​​therebetween. Raw materials with more fiber-type structures are beneficial to improving the compaction density and gram capacity of graphite negative electrode active materials, so that the graphite negative electrode active materials retain a high degree of integrity during the compaction process, and the battery has a good energy density while having a long cycle life; but too high a proportion of fiber-type structures will increase the cost and expansion rate of graphite negative electrode active materials and deteriorate the kinetic performance. Raw materials with a volume proportion of fiber-type structures within the above range have both low costs and good gram capacity for graphite, and the battery cell has a kinetic window for the entire life cycle, thereby comprehensively improving the long-term cycle life and electrochemical performance of the battery.

[0114] By selecting coke raw materials with a fiber-type structure volume ratio greater than or equal to 55% and less than or equal to 70%, under the same graphitization treatment conditions, the crystal structure interlayer spacing of the negative electrode active material is larger, and it has excellent structural stability while having good capacitance; at the same time, the powder compaction density of the carbon-based negative electrode active material is lower (less than 1.65g / cm 3 ), which is beneficial to balance the structural stability and capacitance of carbon-based negative electrode active materials.

[0115] In some embodiments, the maximum gram capacity that can be achieved by the feedstock is greater than the gram capacity of the graphite negative electrode active material.

[0116] High-grade raw materials are used and the degree of graphitization is controlled so that the maximum gram capacity that the raw materials can achieve is not fully utilized, thereby reducing the cycle expansion of the graphite negative electrode active material and improving the cycle stability of the graphite negative electrode active material.

[0117] In some embodiments, the processing of raw materials specifically includes: crushing, shaping and grading the raw materials to obtain a first precursor; granulating the first precursor to obtain a second precursor; and low-temperature carbonizing a mixture of the first precursor and the second precursor to obtain the intermediate product.

[0118] Crushing is the process of reducing the particle size of raw materials. The raw materials can be crushed by any mechanical device such as crusher, mechanical mill, etc.

[0119] Shaping and grading is the process of adjusting the particle size distribution of the raw material to obtain a first precursor that meets the particle size requirements. The particle size and particle size distribution of the first precursor can be regulated by adjusting the grading frequency and the air intake. In some embodiments, the grading frequency during the grading process is 40 Hz-50 Hz, and the air door opening is 20%-70%.

[0120] Granulation is to add a binding material to a set amount of the first precursor for granulation treatment. The binding material can be any substance known in the art that can be used to prepare negative electrode active materials, for example, one or more of coal tar, petroleum asphalt, polymer compounds and resins. After the binding material is heated and melted, the viscosity is not high and good fluidity is maintained, which can reduce the agglomeration of raw material particles in the subsequent preparation process, thereby also reducing the problems of increased surface defects and increased surface active sites of carbon-based negative electrode active material particles due to the need to add a depolymerization process.

[0121] Low-temperature carbonization of the first precursor and the second precursor to obtain the intermediate product includes both low-temperature carbonization of a mixture of the first precursor and the second precursor to obtain the intermediate product and low-temperature carbonization of the first precursor and the second precursor separately to obtain the first intermediate product and the second intermediate product respectively.

[0122] In some embodiments, the volume distribution particle size Dv50 of the first precursor is 6.5 μm to 10.5 μm. In some embodiments, the Dv50 particle size of the first precursor is 6.5 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm, 10.5 μm, or any range therebetween.

[0123] In some embodiments, the particle size distribution of the first precursor (Dv90-Dv10) / Dv50 (or K) is 1.05-1.75. In some embodiments, the particle size distribution of the first precursor is 1.05, 1.15, 1.25, 1.35, 1.45, 1.55, 1.65, 1.75 or any range therebetween.

[0124] In some embodiments, the tap density of the first precursor is 0.55 g / cm 3 ~0.75g / cm 3 .

[0125] In some embodiments, the tap density of the first precursor is 0.55 g / cm 3 , 0.6g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 , 0.75g / cm 3 Or any range of values ​​in between.

[0126] In some embodiments, the Dv50 particle size of the second precursor is 11.0 μm to 15.0 μm.

[0127] In some embodiments, the Dv50 particle size of the second precursor is 11.0 μm, 12.0 μm, 13.0 μm, 14.0 μm, 15.0 μm, or any range therebetween.

[0128] The second precursor is obtained by granulating the first precursor, and therefore, the second precursor mainly forms secondary particles in the graphite negative electrode active material.

[0129] Controlling the particle sizes of the first precursor and the second precursor within the above range helps to achieve the regulation of the particle size and particle size distribution of the graphite negative electrode active material and improve the cycle stability of the battery.

[0130] In some embodiments, the temperature of low temperature carbonization is 900° C.-1300° C., and the time of low temperature carbonization is 24 h-240 h.

[0131] In some embodiments, the temperature of the low temperature carbonization may be selected to be 900° C., 1000° C., 1100° C., 1200° C., 1300° C., or any range therebetween.

[0132] In some embodiments, the low-temperature carbonization time may be 24 h, 50 h, 75 h, 100 h, 150 h, 200 h, 240 h, or any range therebetween.

[0133] In some embodiments, the graphitized product of the first precursor and the second precursor are mixed in a mass ratio of (1:1) to (6:4) to obtain a carbon-based negative electrode active material. This improves the chemical mechanical properties of the negative electrode active material during the cycle, and can also make the negative electrode membrane have a suitable pore structure, reduce the irreversible consumption of active ions and improve the transmission performance of active ions, thereby improving the cycle performance of the secondary battery.

[0134] In some embodiments, after the precursor is graphitized, it is further sieved and demagnetized.

[0135] In some embodiments, the primary particle graphitization product and the secondary particle graphitization product after screening and demagnetization are mixed in a mass ratio of (1:1) to (6:4), for example, 50:50, 55:45 or 60:40.

[0136] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0137] In one embodiment of the present application, a secondary battery is provided.

[0138] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0139] [Positive electrode]

[0140] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0141] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0142] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0143] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622)、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0144] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0145] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0146] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0147] [Negative electrode]

[0148] The negative electrode plate comprises a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, wherein the negative electrode film layer comprises the above-mentioned carbon-based negative electrode active material.

[0149] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0150] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned carbon-based negative electrode active materials. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, other artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0151] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0152] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0153] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0154] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0155] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, a negative electrode sheet including a negative electrode film layer can be obtained.

[0156] In some embodiments, the compaction density of the negative electrode film layer is 1.5 g / cm 3 ~1.65g / cm 3In some embodiments, the compaction density of the negative electrode film layer is 1.55 g / cm 3 ~1.65g / cm 3 The compaction density of the negative electrode film layer within the above range is helpful to control the energy density of the secondary battery, thereby improving the cycle performance of the secondary battery.

[0157] In some embodiments, the specific surface area of ​​the negative electrode film layer is 0.7 m 2 / g~2m 2 / g, optional 1.0m 2 / g~1.6m 2 The specific surface area of ​​the negative electrode film layer within the above range is helpful to control the contact area between the negative electrode film layer and the electrolyte, reduce the side reaction of the carbon-based negative electrode active material in the negative electrode sheet, reduce the irreversible consumption of active ions, and thus improve the cycle performance of the secondary battery.

[0158] In some embodiments, the porosity of the negative electrode film layer is 0.22 to 0.42, and can be 0.27 to 0.37. The porosity of the negative electrode film layer within the above range helps to reduce the migration resistance of active ions and electrons and improve the kinetic performance of the secondary battery.

[0159] The compaction density of the negative electrode film layer can be tested by methods known in the art. As an example, an electronic balance is used to weigh a negative electrode sheet test sample with an area of ​​S, and the weight is recorded as W1, and a micrometer is used to measure the thickness T1 of the negative electrode sheet. Then the weighed electrode sheet film layer is wiped off, the weight of the negative electrode current collector is weighed, recorded as W2, and the thickness T2 of the negative electrode current collector is measured using a micrometer. Then the compaction density of the negative electrode film layer PD = (W1-W2) / [(T1-T2)×S].

[0160] The specific surface area of ​​the negative electrode film layer can be tested by methods known in the art. As an example, the specific surface area determination method of GB / T 19587-2017 can be referred to, and the specific surface area of ​​the negative electrode film layer can be measured by a specific surface area analyzer (such as the American Micromeritics TriStar 3020) by nitrogen adsorption / desorption method: the negative electrode film layer is dried in a vacuum drying oven and then placed in a sample tube, and measured in the analyzer.

[0161] The porosity P of the negative electrode film layer can be tested by methods known in the art. As an example, referring to GB / T21650.2-2008, the porosity P of the negative electrode sheet is measured by nitrogen adsorption method, that is, the percentage of the pore volume in the negative electrode sheet to the total volume of the negative electrode sheet: the calculation formula is P = (V1-V2) / V1×100%, where V1 is the apparent volume of the electrode sheet sample, and V2 is the actual volume of the electrode sheet sample. Among them, the apparent volume V1 of the electrode sheet sample is calculated by the formula V1 = S×H×A, where S is the area of ​​the negative electrode sheet (unit: cm2); H is the thickness of the negative electrode sheet (unit: cm); A is the number of samples (unit: ea). The specific test steps are as follows: in a conventional laboratory environment, use tweezers to select no less than 20 electrode discs with good appearance and no powder falling on the edges and put them into the sample cup, record the number of pieces, and calculate the apparent volume V1; after the sample electrode is placed in a 3.5cm3 sample cup, it is placed in a true density tester, a closed test system, and ammonia is introduced according to the procedure. By detecting the pressure of the gas in the sample chamber and the expansion chamber, the real volume V2 is calculated according to Bohr's law (PV=nRT), thereby obtaining the porosity of the negative electrode film layer to be tested.

[0162] [Electrolytes]

[0163] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0164] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0165] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0166] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0167] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0168] [Isolation film]

[0169] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0170] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0171] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0172] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0173] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0174] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0175] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0176] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0177] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0178] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0179] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0180] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0181] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0182] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0183] Figure 6The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0184] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0185] Example

[0186] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0187] 1. Negative electrode active materials and secondary battery performance test

[0188] 1. Powder compaction density test

[0189] According to GB / T 24533-2009, weigh 1g of negative electrode active material powder and add a bottom area of ​​1.327cm 2 The mold is pressurized to 20000N, maintained for 30s, then released and maintained for 10s, and the powder compaction density of the negative electrode active material under a pressure of 20000N is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).

[0190] According to GB / T 24533-2009, weigh 1g of negative electrode active material powder and add a bottom area of ​​1.327cm 2 The mold is pressurized to 49000N, maintained for 30s, then released and maintained for 10s. The powder compaction density of the carbon material under a pressure of 49000N is measured by an electronic pressure testing machine (such as UTM7305 electronic pressure testing machine).

[0191] 2. Powder particle size test and particle size distribution test

[0192] Determination method: Referring to GB / T 19077-2016 particle size distribution laser diffraction method, a laser particle size analyzer such as Mastersizer 2000E of Malvern Instruments Ltd. of the United Kingdom was used for determination to obtain volume distribution particle diameters Dv10, Dv50, Dv90, and particle size distribution.

[0193] 3. Negative electrode active material gram capacity test

[0194] The negative electrode active material sample, the conductive agent carbon black, and polyvinylidene fluoride (PVDF) were fully stirred and mixed in an appropriate amount of solvent NMP according to a mass ratio of 91.6:1.8:6.6 to form a uniform negative electrode slurry; the negative electrode slurry was evenly coated on the surface of the negative electrode current collector copper foil and dried and cold pressed; then the metal lithium sheet was used as the counter electrode, and the polypropylene (PP) film was used as the isolation membrane, and the electrolyte was injected. The electrolyte formula used was as follows: dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) were mixed according to a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 was dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L. CR2430 button cells were assembled in an argon-protected glove box. At 25°C, the button cell prepared above was first discharged at a constant current of 0.05C to 0.005V, then discharged at a constant current of 10μA to 0.005V, and left to stand for 5 minutes, and the first cycle discharge capacity of the button cell was recorded; then, the button cell was charged at a constant current of 0.1C to 2.0V, and the charging capacity of the button cell was recorded. The ratio of the charging capacity of the button cell to the mass of the negative electrode active material sample is the gram capacity of the negative electrode active material.

[0195] 4. Cycle performance test of secondary batteries

[0196] At 60°C, the prepared secondary battery was charged at a constant current of 1C to a voltage of 3.65V, then charged at a constant voltage of 3.65V to a current ≤ 0.05C, and then the battery was discharged at a constant current of 1C to a voltage of 2.5V. This was a charge and discharge process, and the discharge capacity C1 of the first cycle was recorded. The charge and discharge cycles were repeated until the battery capacity decayed to 80% of the initial capacity C1, and the test was stopped, and the number of cycle tests was recorded.

[0197] 5. Test on the volume ratio of fiber structure in coke raw materials

[0198] Take the raw materials according to GB 1997-89, mix the raw materials crushed to 1mm, shrink and separate 40g~50g, use a square hole sieve to take 4g~5g of 0.07mm~1.0mm grade samples for film making; prepare powder coke and block coke light films according to MT 116.1-86, the diameter of the powder coke light film shall not be less than 22mm, and the volume occupied by the cement shall be less than 1 / 3; place the sample on a slide with cement, flatten it, and then place it on the stage to align the focus, calibrate the microscope, and adjust the polarizer and analyzer to make them orthogonal. Insert the azurite inspection plate (1λ) so that the field of view presents the interference color of primary red; determine the step length of the moving ruler to ensure that more than 400 effective measuring points are evenly distributed, and the point spacing is 0.3~0.5mm and the line spacing is generally 0.5~0.8mm. Starting from one end of the sample, determine the type of microstructure under the intersection of the crosshairs, and divide the number of effective measuring points of the fiber-type structure optical organization by the total number of statistical testing points as the volume proportion of the fiber-type structure in the raw material.

[0199] 2. Preparation of secondary batteries

[0200] Example 1

[0201] 1) Preparation of carbon-based negative electrode active materials

[0202] The needle coke with a volume ratio of 61.0% of the fiber structure is crushed; the crushed material is shaped and finely powdered to obtain the first precursor. The Dv50 particle size of the first precursor is 9.4μm, the particle size distribution (Dv90-Dv10) / Dv50 is 1.19, and the tap density of the first precursor is 0.68g / cm 3 .

[0203] The first precursor is granulated and reformed in a reactor to obtain a second precursor having a particle size Dv50 of 14.1 μm;

[0204] The first precursor and the second precursor were placed in a kiln for carbonization at a carbonization temperature of 1100°C and a high temperature zone time of 24 hours to obtain a first intermediate product and a second intermediate product, respectively. The tap density of the first intermediate product was 0.96 g / cm 3 The tap density of the second intermediate product is 0.92g / cm 3 ;

[0205] The first intermediate product and the second intermediate product are graphitized at a temperature of 2800°C respectively. The graphitization treatment device is an internal series furnace with a rated power of 28000W. The maximum power of the graphitization treatment is 22400W. The constant power duration of the maximum power is maintained for 24 hours to obtain primary particles and secondary particles respectively.

[0206] The primary particles and the secondary particles are uniformly mixed in a mass ratio of 50:50, and the final product, graphite negative electrode active material, is obtained by sieving and removing magnetism.

[0207] The compaction density of the graphite negative electrode active material at 20000N is 1.61g / cm 3 , the graphitization degree is 92.48%, and the specific surface area is 1.47m 2 / g, the volume distribution particle size Dv50 is 10.3μm, and the powder compaction density under a pressure of 49000N is 1.82g / cm 3 The gram capacity is 350 mAh / g, ID / IG is 0.075, the interlayer spacing d1 of the surface area is 0.3373, the interlayer spacing d2 of the internal area is 0.3360 nm, and the particle size distribution (Dv90-Dv10) / Dv50 is 1.36.

[0208] 2) Preparation of positive electrode

[0209] The positive electrode active material lithium iron phosphate (LFP), the conductive agent Super P, and the binder PVDF are mixed in a mass ratio of 97:1:2, and the solvent N-methylpyrrolidone is added and stirred evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, cold pressing, and cutting. The compaction density of the positive electrode sheet is 2.5g / cm 3 .

[0210] 3) Preparation of negative electrode sheet

[0211] The prepared carbon-based negative electrode active material, conductive agent Super P, thickener sodium carboxymethyl cellulose, and binder styrene butadiene rubber were mixed in a mass ratio of 96:1:1.2:1.8, and deionized water was added as a solvent, and stirred evenly to obtain a negative electrode slurry; the negative electrode slurry was evenly coated on the negative electrode current collector copper foil, dried, cold pressed, and cut to obtain a negative electrode sheet. The compaction density of the negative electrode film layer is 1.6g / cm 3 , the surface density is 9.48mg / cm 2 .

[0212] 4) Preparation of electrolyte

[0213] In an argon atmosphere glove box with a water content of <10ppm, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and ethylene carbonate (EC) are mixed in a weight ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1.0 mol / L, and then vinylene carbonate (VC) is added, and the content of VC is 2% of the total mass of the electrolyte.

[0214] 5) Isolation film

[0215] A polypropylene film is selected as the isolation film.

[0216] 6) Preparation of secondary batteries

[0217] The positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0218] Examples 2 to 7 and Comparative Examples 1 to 4

[0219] The preparation steps of Examples 2 to 7 and Comparative Examples 1 to 4 are similar to those of Example 1, but the preparation parameters of the negative electrode active materials are adjusted, see Table 1-1 and Table 1-2 for details.

[0220] Table 1-1: Preparation parameters of negative electrode active materials of Examples 1 to 7 and Comparative Examples 1 to 4

[0221]

[0222] Table 1-2: Preparation parameters of negative electrode active materials of Examples 1 to 7 and Comparative Examples 1 to 4

[0223]

[0224] The negative electrode active materials and secondary batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 4 were tested using the above test method, and the results are shown in Table 2 below:

[0225] Table 2: Parameter test and performance test results of Examples 1 to 7 and Comparative Examples 1 to 4

[0226]

[0227] It can be seen from Examples 1 to 7 and Comparative Examples 1 to 4 that when the gram capacity of the negative electrode active material is in the range of 345 mAh / g to 355 mAh / g, the powder compaction density of the negative electrode active material under a pressure of 20000 N is 1.55 g / cm 3 ~1.65g / cm 3 The secondary battery prepared using the negative electrode active material has a high number of cycles at 60°C, indicating that the secondary battery has good cycle performance.

[0228] In Comparative Example 1, the gram capacity of the negative electrode active material is 358.1 mAh / g, and the powder compaction density of the negative electrode active material under a pressure of 20000N is increased to 1.72 g / cm 3 However, the number of cycles of the secondary battery is only 1573, indicating that the compaction density of the negative electrode active material under a pressure of 20000N exceeds 1.65g / cm 3When the gram capacity exceeds 355mAh / g, it is not conducive to improving the cycle performance of the secondary battery.

[0229] In Comparative Example 2, the gram capacity of the negative electrode active material is 348.5 mAh / g. When all the negative electrode active materials are primary particles, the powder compaction density of the negative electrode active material under a pressure of 20000N is increased to 1.67 g / cm 3 However, the number of cycles of the secondary battery is only 1650, indicating that the powder compaction density of the negative electrode active material under a pressure of 20000N exceeds 1.65g / cm 3 After that, it can affect the cycle performance of the secondary battery.

[0230] In Comparative Example 3, when the gram capacity of the negative electrode active material is 353.7 mAh / g, the powder compaction density of the negative electrode active material under a pressure of 20000 N is increased to 1.69 g / cm 3 However, the number of cycles of the secondary battery is only 1621, indicating that the compaction density of the negative electrode active material under a pressure of 20000N exceeds 1.65g / cm 3 After that, it can affect the cycle performance of the secondary battery.

[0231] In Comparative Example 4, when the gram capacity of the negative electrode active material is 350.3 mAh / g, the powder compaction density of the negative electrode active material under a pressure of 20000 N is reduced to 1.54 g / cm 3 The number of cycles of the secondary battery is only 1605, indicating that the compaction density of the negative electrode active material under a pressure of 20000N is lower than 1.55g / cm 3 After that, the cycle performance of the secondary battery is poor.

[0232] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A carbon-based negative electrode active material, characterized in that: The gram capacity of the carbon-based negative electrode active material is 345 mAh / g to 355 mAh / g, and the powder compaction density under a pressure of 20000 N is 1.55 g / cm 3 Above and less than 1.65g / cm 3 .

2. The carbon-based negative electrode active material according to claim 1, characterized in that: The powder compaction density of the carbon-based negative electrode active material under a pressure of 20000N is 1.57g / cm 3 ~1.62g / cm 3 Alternatively, the powder compaction density of the carbon-based negative electrode active material under a pressure of 49000N is 1.73g / cm 3 Above and less than 1.84g / cm 3 .

3. The carbon-based negative electrode active material according to claim 1 or 2, characterized in that: The gram capacity of the carbon-based negative electrode active material is 346 mAh / g to 353 mAh / g.

4. The carbon-based negative electrode active material according to any one of claims 1 to 3, characterized in that: The carbon-based negative electrode active material includes primary particles and secondary particles; optionally, the amount of the primary particles in the carbon-based negative electrode active material is greater than or equal to the amount of the secondary particles in the carbon-based negative electrode active material.

5. The carbon-based negative electrode active material according to any one of claims 1 to 4, characterized in that: The carbon-based negative electrode active material satisfies at least one of the following conditions: a) Particle size distribution K is 1.0-1.6, and can be selected as 1.1-1.5, K = (Dv90-Dv10) / Dv50; b) Volume distribution particle size Dv50 is 8 μm to 13 μm, and can be 9 μm to 12 μm; c) The degree of graphitization is 88% to 95%, and can be optionally 90% to 95%.

6. The carbon-based negative electrode active material according to any one of claims 1 to 5, characterized in that: The specific surface area of ​​the carbon-based negative electrode active material is 1.25 m 2 / g~1.95m 2 / g, optional 1.25m 2 / g~1.85m 2 / g.

7. The carbon-based negative electrode active material according to any one of claims 1 to 6, characterized in that: The tap density of the carbon-based negative electrode active material is 1.07 g / cm 3 ~1.27g / cm 3 .

8. The carbon-based negative electrode active material according to any one of claims 1 to 7, characterized in that: The carbon-based negative electrode active material is artificial graphite.

9. A method for preparing a carbon-based negative electrode active material, characterized in that: The following steps are involved: Provide raw materials; Processing the raw materials to obtain intermediates; performing graphitization treatment on the intermediate to obtain a graphitized product; Screening the graphitized product to obtain a carbon-based negative electrode active material; The gram capacity of the carbon-based negative electrode active material is 345 mAh / g to 355 mAh / g, and the powder compaction density under a pressure of 20000 N is 1.55 g / cm 3 Above and less than 1.65g / cm 3 .

10. The preparation method according to claim 9, characterized in that: The graphitization treatment satisfies at least one of the following conditions: (1) The maximum power of the graphitization treatment is 70%-90% of the rated power of the graphitization treatment equipment; (2) The temperature of the graphitization treatment is 2600° C. to 3000° C.; (3) The graphitization treatment time is 10 h to 50 h.

11. The preparation method according to claim 9 or 10, characterized in that: The raw materials include one or more of petroleum coke, needle coke, and asphalt coke, and can optionally include needle coke.

12. The preparation method according to claims 9 to 11, characterized in that: Based on the total volume of the raw material, the volume proportion of the fiber-type structure in the raw material is greater than or equal to 55%, and can be optionally 58%-70%.

13. The preparation method according to any one of claims 9 to 12, characterized in that: The processing of raw materials specifically comprises the following steps: crushing, shaping and classifying the raw materials to obtain a first precursor; Granulating the precursor to obtain a second precursor; The first precursor and the second precursor are carbonized at low temperature to obtain the intermediate product.

14. The preparation method according to claim 13, characterized in that: The first precursor satisfies at least one of the following conditions: (1) The Dv50 particle size of the first precursor is 6.5 μm to 10.5 μm; (2) the particle size distribution of the first precursor (Dv90-Dv10) / Dv50 is 1.05 to 1.75; (3) The tap density of the first precursor is 0.55 g / cm 3 ~0.75g / cm 3 .

15. The preparation method according to claim 13, characterized in that: The volume distribution particle size Dv50 of the second precursor is 11 μm to 15 μm.

16. The preparation method according to any one of claims 13 to 15, characterized in that: The first precursor and the graphitized product of the second precursor are mixed in a mass ratio of (1:1) to (6:4).

17. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes the carbon-based negative electrode active material described in any one of claims 1 to 8 or the carbon-based negative electrode active material prepared by the method described in any one of claims 9 to 16.

18. The secondary battery according to claim 17, characterized in that: The negative electrode plate satisfies at least one of the following conditions: (1) The compaction density of the negative electrode film layer is 1.5 g / cm 3 ~1.65g / cm 3 , optional 1.55g / cm 3 ~1.65g / cm 3 ; (2) The specific surface area of ​​the negative electrode film layer is 0.7 m 2 / g~2m 2 / g, optional 1.0m 2 / g~1.6m 2 / g; (3) The porosity of the negative electrode film layer is 0.22 to 0.42, and can be optionally 0.27 to 0.

37.

19. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 17 or 18.

Citation Information

Patent Citations

  • Negative active material, method for preparing same, secondary battery, and battery module, battery pack and device including secondary battery

    CN114730875A

  • Secondary battery, battery module including same, battery pack, and device

    CN114902450A

  • Carbon secondary particle and preparation method thereof, artificial graphite and preparation method thereof, lithium ion battery negative electrode material and lithium ion battery

    CN115432698A

  • Quick-charge type negative electrode active material and preparation method thereof, negative electrode plate, secondary battery and electric device

    CN116806376A

  • Negative electrode for lithium secondary battery and manufacturing method thereof

    KR102536147B1